TINJAUAN AZ ZARNUJI TERKAIT RELEVANSI KEWAJIBAN DAN HAK SISWA DALAM KONTEKS PENDIDIKAN MODERN - Yugo, Tri Yugo (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This study aims to examine Imam Az-Zarnuji's views on the obligations and rights of students in the context of the book "Ta'lim Muta'allim" and evaluate its relevance in modern education. The main focus of this research is to understand how traditional Islamic education principles can be applied to overcome the challenges faced in the contemporary education system. The research method used is an in-depth literature review method to collect and analyze data through qualitative text analysis, where the main data is obtained from an in-depth reading of the book "Ta'lim Muta'allim" and is complemented by secondary data from relevant literature. The analysis process involves identifying key themes, such as sincere learning intentions, manners and ethics, consistency in learning, and the right to a fair and inclusive education. The results of the study show that the principles proposed by Az-Zarnuji, such as the importance of sincere intention in pursuing knowledge, respect for teachers, and diligent effort, have strong relevance to modern educational values that emphasize character development and intrinsic motivation. The novelty of this research lies in the interdisciplinary approach that connects the concept of traditional Islamic education with modern educational practices and theories, which has not been widely discussed in previous studies. Thus, this research makes a significant contribution in understanding how the integration between traditional and modern education can improve the quality of education and holistic student development. Keywords: Obligations; Rights; Student; Ta'lim Muta'allim.